2019
DOI: 10.5194/acp-19-8407-2019
|View full text |Cite
|
Sign up to set email alerts
|

Sea salt aerosol production via sublimating wind-blown saline snow particles over sea ice: parameterizations and relevant microphysical mechanisms

Abstract: Blowing snow over sea ice has been proposed as a significant source of sea salt aerosol (SSA) (Yang et al., 2008). In this study, using snow salinity data and blowing snow and aerosol particle measurements collected in the Weddell Sea sea ice zone (SIZ) during a winter cruise, we perform a comprehensive model-data comparison with the aim of validating proposed parameterizations. Additionally, we investigate possible physical mechanisms involved in SSA production from blowing snow. A global chemical transport m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(82 citation statements)
references
References 63 publications
4
77
1
Order By: Relevance
“…The ozone photochemistry scheme applied to the model has been detailed in previous studies (Law et al, 1998(Law et al, , 2000Savage et al, 2004), with updates including an isoprene chemistry scheme, same as the one implemented in the UKCA model by Young et al (2009) according to the method of Pöschl et al (2000); a hydrolysis reaction of N 2 O 5 on aerosols and cloud droplets (Yang et al, 2005); a tropospheric-bromine scheme involving both gaseous-phase reactions (Yang et al, 2005) and heterogeneous reactions (Yang et al, 2010); and a Fast-J photolysis scheme developed by Voulgarakis et al (2009b), which is not used in this study. They found that N 2 O 5 hydrolysis can cause net NO x loss at high latitudes by up to 60 % in the Northern Hemisphere and ∼ 80 % in the Southern Hemisphere (Yang et al, 2005).…”
Section: P-tomcat Modelmentioning
confidence: 99%
“…The ozone photochemistry scheme applied to the model has been detailed in previous studies (Law et al, 1998(Law et al, , 2000Savage et al, 2004), with updates including an isoprene chemistry scheme, same as the one implemented in the UKCA model by Young et al (2009) according to the method of Pöschl et al (2000); a hydrolysis reaction of N 2 O 5 on aerosols and cloud droplets (Yang et al, 2005); a tropospheric-bromine scheme involving both gaseous-phase reactions (Yang et al, 2005) and heterogeneous reactions (Yang et al, 2010); and a Fast-J photolysis scheme developed by Voulgarakis et al (2009b), which is not used in this study. They found that N 2 O 5 hydrolysis can cause net NO x loss at high latitudes by up to 60 % in the Northern Hemisphere and ∼ 80 % in the Southern Hemisphere (Yang et al, 2005).…”
Section: P-tomcat Modelmentioning
confidence: 99%
“…A process-based SSA transport, dry and wet deposition scheme has been implemented in the model by Levine et al (2014) based on the work of Reader and McFarlane (2003). The open ocean sea spray emission scheme follows Jaeglé et al, (2011), and the sea-ice-sourced SSA scheme follows the latest work of Yang et al (2019). Both open-ocean-sourced and sea-icesourced SSA (denoted as OO and SI, respectively) are tagged in 21 size bins covering dry NaCl diameter of 0.02-20 μm in 35 order to track their history for online calculation of their surface density for heterogeneous reaction rates.…”
Section: P-tomcat Modelmentioning
confidence: 99%
“…We assume that the evaporation rate of blowing snow particles is controlled by the moisture gradient between the surface of the particle and the ambient air, i.e., the classic mechanism in Yang et al (2019). Other physical parameters include blowing snow size distribution (a shape parameter α=3 and a scale parameter β=37.5 µm), SSA production ratio N =20 (i.e., 20 SSA particles formed from one saline wind-blown snow particle during sublimation).…”
Section: P-tomcat Modelmentioning
confidence: 99%
See 2 more Smart Citations